Leukotoxicity of Aggregatibacter actinomycetemcomitans in generalized aggressive periodontitis in Brazilians and their family members - Souza Silveira, Virginia Regia; Bessa Nogueira, Marcia Viana; Pinto Nogueira, Nadia Accioly; Lima, Vilma; Chaves Furlaneto, Flavia Aparecida [UNESP]; Rego, Rodrigo Otavio (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2013)
Objective: The purpose of this study was to examine the leukotoxin promoter types of Aggregatibacter actinomycetemcomitans clones in subjects with generalized aggressive periodontitis (GAgP) and in their family members (FM). Material and Methods: Thirty-five patients with GAgP (33.9+/-7.1 years), 33 of their FM (22.8+/-11.4 years), and 41 patients with chronic periodontitis (CP) (44.1+/-9.4 years) were clinically analyzed using the plaque index, gingival index, probing depth (PD), and clinical attachment level (CAL). Subgingival biofilm samples were collected from four interproximal periodontal sites (>PD and >CAL) of each patient. The presence of A. actinomycetemcomitans and its leukotoxic clone was confirmed by polymerase chain reaction (PCR). Results: A. actinomycetemcomitans was observed in 23 (51.1%) GAgP patients and 16 (30.1%) CP patients. Thirty-seven (94.8%) patients showed minimally leukotoxic strains and 2 (5.1%) showed highly leukotoxic strains. In the FM group, 10 (30.3%) had aggressive periodontitis (AgP), 12 (36.3%) had CP, 11 (33.3%) were periodontally healthy or had gingivitis, and 12.2% were A. actinomycetemcomitans positive. Greater full mouth PD and CAL were observed in GAgP patients positive for the bacteria than those negative for it (p<0.05), and the presence of A. actinomycetemcomitans positively correlated with GAgP (Odds ratio, 3.1; confidence interval, 1.4-7.0; p=0.009). Conclusions: The presence of A. actinomycetemcomitans was associated with the clinical condition of GAgP, with most patients exhibiting a generalized form of the disease and minimally leukotoxic clones. Most of the relatives of GAgP patients presented either CP or AgP.
Keywords: Aggregatibacter actinomycetemcomitans; Leukotoxin; Periodontitis